A resilient and flexible chitosan/silk cryogel incorporated Ag/Sr co-doped nanoscale hydroxyapatite for osteoinductivity and antibacterial properties. Issue 45 (22nd October 2018) - Li, Pengfei; Jia, Zhanrong; Wang, Qun; Tang, Pengfei; Wang, Menghao; Wang, Kefeng; Fang, Ju; Zhao, Cancan; Ren, Fuzeng; Ge, Xiang; Lu, Xiong
Abstract : A resilient and flexible chitosan/silk cryogel incorporated Ag and Sr co-doped hydroxyapatite exhibits good mechanical, antibacterial and osteoinductive properties. Abstract : Cryogels from natural biopolymers, especially chitosan (CS) and silk fibroin (SF), have attracted significant attention for bone tissue engineering due to their good biocompatibility and tissue affinity. However, they are still not widely applied in clinics because of their poor mechanical properties, and lack of osteoinductivity and antibacterial properties. Here, by integrating a physico-chemical hybrid-crosslinking strategy and a freeze-drying method, the authors have prepared a resilient and flexible chitosan/silk cryogel with Ag and Sr co-doped hydroxyapatite (AgSrHA). The cryogel exhibits super resilience and flexibility, which guarantees the mechanical strength required for bone repair. Furthermore, the cryogel possesses long-term effective antibacterial properties and osteoinductivity due to the slow release of Ag and Sr ions. The physico-chemical hybrid-crosslinking points were introduced into a CS/SF network by treating with a mixture of alkaline and polyethylene glycol glycidyl ether (PEGDE) at 60 °C, which endowed the cryogel with super resilience and flexibility. Nanoscale AgSrHA was incorporated into the CS/SF network to further enhance the mechanical properties of the cryogel. In addition, Ag and Sr were doped into the HA crystal lattice, which not only prevents cytotoxicity by avoiding the ion burst release behavior, but also can achieve antibacterial and osteoinductive properties for a long period of time. In short, the AgSrHA/CS/SF cryogel with excellent mechanical properties and long-term effective dual-biofunction of antibacterial properties and osteoinductivity would be an ideal candidate for successful bone repair in clinics.